A Comprehensive Systematic Review: Radiological Characteristics of Respiratory Distress Syndrome (RDS) Versus Transient Tachypnea of the Newborn (TTN) on Neonatal Chest Radiographs - Ahmad Fauzi; Gani Michel; Nunung Nuripah; Zemmy Dison Bira (International Medical Journal Corp. Ltd, 2026)
Introduction: RDS and TTN are the two most frequent causes of early neonatal respiratory failure, traditionally differentiated by chest radiography (CXR). RDS results from surfactant deficiency with alveolar collapse, while TTN results from delayed fetal lung fluid clearance. Both differ in prognosis and surfactant need, yet their radiographic signs overlap substantially in the first hours of life. Methods: A systematic review was conducted in accordance with PRISMA 2020. Eligible designs were RCTs, cohort, case-control, cross-sectional, and observational studies. Risk of bias was appraised with QUADAS-2, Newcastle-Ottawa Scale and RoB 2. A structured narrative synthesis with descriptive quantitative pooling across fourteen outcome domains was undertaken. Results: Twenty-nine studies (>350,000 neonates, >43,000 CXRs) included. Ground-glass/reticulogranular in 83.6%, air bronchograms 70.9%, reduced lung volume 66.4% in RDS; consolidation with air bronchograms exclusive to RDS (sensitivity & specificity 100%). TTN characterised by interstitial fluid without consolidation (99.5% on serial exams). CXR alone performed lower: sensitivity 38.9%, specificity 77.8% for predicting NIV failure, AUC 0.80 for surfactant need (vs LUS 88.9%/100% and AUC 0.94). Each 1-point CXR score increase raised BPD odds by 77.7% (OR 1.777; p=0.001). Deep-learning F1 score 90.30% for RDS vs 70.84% for TTN. Discussion: The radiographic distinction between RDS and TTN rests on a small number of high-value discriminators—consolidation with air bronchograms and homogeneous granular hypoaeration for RDS, versus interstitial/perihilar fluid patterns with preserved or increased lung volume for TTN—but the plain radiograph is limited by low interobserver reliability, delayed acquisition, radiation exposure and a systematic tendency to misclassify early or mild disease. The evidence is consistent that CXR retains an irreplaceable confirmatory and complication-detection role, particularly in low-resource settings, while surrendering its position as the sole first-line arbiter of surfactant decisions. Conclusion: Chest radiography discriminates RDS from TTN with high specificity when consolidation and air bronchograms are present, but with insufficient sensitivity in the first hours of life to serve alone as the basis for surfactant decisions. Radiographic severity is a genuinely graded prognostic marker. A hybrid pathway—radiographic confirmation combined with quantitative bedside lung ultrasound and structured severity grading—is recommended, together with prospective studies using explicit, blinded, radiograph-only feature extraction.